Políticas públicas de legalización de tierras y su efecto en el derecho de propiedad privada en el cantón Quevedo - Ríos Cedeño, Álvaro Ernesto (2022)
viii SUMMARY The present investigation had as objective to establish the public policies of land legalization in the right of private property in the Quevedo canton. The study was developed in the Quevedo canton of the province of Los Ríos. A significant sample of the total population of the Quevedo canton was extracted, determining a total of 384 inhabitants, to whom the survey was applied with closed questions using the Google Forms tool. The results obtained show that citizens have a good perception of public land legalization policies in the Quevedo canton, since some facilities and priorities are given to people who need them for the correct execution of their property titling procedures. therefore, they expressed a high degree of satisfaction with the aforementioned policies.